TEACHING DESCRIPTIVE TEXT WRITING THROUGH GUIDED WH-QUESTIONS: A Pre-experimental Study At The Eight Grade Students of SMP Negeri 7 Pontianak In Academic Year 2013/2014 - Mutiara, Rafika (IKIP-PGRI Pontianak, 2014)
The purpose of conducting this research is to answer the research questions which are, âIs the use of guided WH-Questions technique effective in teaching descriptive text writing at the eighth grade students of SMPN 7 Pontianak in academic year of 2013/2014?â and âHow effective is the use of guided WH-Questions technique in teaching descriptive text writing at the eighth grade students of SMPN 7 Pontianak in academic year of 2013/2014?â The form of this research is pre-experimental study. The tool of data colleting was written test, in which the students were asked to write a descriptive text by the help of guided WH-Questions. The sample of this research was 35 students from Class VIII C. The findings of this research showed that the use of guided WH-Questions technique in teaching descriptive text writing was effective.Based on the calculation that the researcher has gotten, it also showed that the score of Effect Size was high. So, it indicated that the effect of guided WH-Questions technique in teaching descriptive text writing was highly effective. From that effective result, the researcher suggests that guided WH-Questions technique can be used in teaching English especially in writing skill.